Knowledge and Attitude of Long Vacation Training Students Towards Solid Waste Management at Ahmadu Bello University, Zaria - Yabagi, Muhammad (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
Poor sustainable waste management practices in some Nigerian Universities constitute one of the major factors leading to declining environmental health conditions of University communities. Sustainable waste management practices are needed to ensure the protection of the environment and students’ health. Few studies have captured sustainable waste practices problems in Nigerian educational institutions, particularly the views of students in schools. This study was designed to assess the knowledge and attitude of Long Vacation Training (LVT) students of Ahmadu Bello University (ABU), Zaria, towards sustainable waste disposal practices. Using a sample size of 60 LVT students 2023/2024 Session, consisting of 30 males and 30 females. The researcher randomly selected this sample to represent the entire population of 300 LVT students in the 2023 academic year. A structured questionnaire was used to collect data and was analysed using percentage, mean and standard deviation with a decision rule of 2.50. The study found that the majority of ABU LVT students have good knowledge of sustainable solid waste management practices. It was also discovered that a greater number of ABU LVT students have a poor attitude towards sustainable solid waste management within the University environment.